Human Resource Management Strategy to Improve Sustainable Company per Formance In Industry 4.0 at the Organization of PT. KAI Daop 2 Bandung - Sakti, Hudan Malik Bhuanan; Kanji, Muhammad Syahrul; Suprapto, Ryan Puspo; Wijaya, Aprilia Lintang; Danistyarini, Pundy; Sekarini, Ratih Ayu (PT FORMOSA CENDEKIA GLOBAL, 2025)
Human resources are an important factor in improving company performance. Competing in the world of work Companies must be able to implement a Human Resource Management Strategy about Industry 4.0 in the Company Organization. The purpose of this study was to determine whether Motivation (X1) and Training (x2) have a significant effect on Company Performance (Y) at PT. Kai Daop 2 Bandung. Thenformulate the right Human Resources Management Strategy to improve sustainable Company Performance in Industry 4.0. The population in this study were all employees at Daop 2 Bandung station. The sample used in this study was 55 employees as respondents. The method in this study uses a Quantitative method with a Correlational approach. The results of the research and hypothesis show that Motivation (X1) and Training (X2) have a positive and significant effect on Company Performance (Y) at PT Kai Daop 2 Bandung.